Crime control and community the new politics of public safety - Hughes, Gordon 1952-; Edwards, Adam (Routledge, 2012)
Community-based crime control has become one of the principal policy responses to crime and disorder across western societies, and is regarded now as one of the keys to successful crime prevention and reduction. The aim of this book is to bring together findings from case studies of community-based crime control in England as a means of examining the prospects for this approach, its evolving relationship with criminal justice and social policies, and to assess the lessons internationally that can be drawn from this in the theory, research methods, politics and practice of crime control. At the same time the book advances an important new conceptual framework for understanding community-based crime control, focusing on an understanding of the diversity of control and preventative strategies, the locally particular conditions in which they are conducted, and the degree of choices open to local political actors involved in their conduct. Understanding diversity in this way is central to drawing lessons about the transferability of crime control theory and practice from one social context to another, avoiding the naive emulation of practices in different contexts.